2013
DOI: 10.1117/1.jbo.18.5.056007
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive optics optical coherence tomography forin vivomouse retinal imaging

Abstract: Abstract. Small animal models of retinal diseases are important to vision research, and noninvasive high resolution in vivo rodent retinal imaging is becoming an increasingly important tool used in this field. We present a custom Fourier domain optical coherence tomography (FD-OCT) instrument for high resolution imaging of mouse retina. In order to overcome aberrations in the mouse eye, we incorporated a commercial adaptive optics system into the sample arm of the refractive FD-OCT system. Additionally, a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…[20][21][22] The high resolution of third-generation spectral-domain OCT devices renders in vivo retinal imaging in mice and rats possible, gaining an increasing importance in ophthalmological and neurological preclinical research. [23][24][25][26][27][28][29][30][31][32][33] The obtained results are in good accordance with histological sections of the animals' retinae. 34 The application of OCT technology in rodent models, however, is still challenging, mainly because of the small size of the rodents' eyes.…”
Section: Introductionsupporting
confidence: 81%
“…[20][21][22] The high resolution of third-generation spectral-domain OCT devices renders in vivo retinal imaging in mice and rats possible, gaining an increasing importance in ophthalmological and neurological preclinical research. [23][24][25][26][27][28][29][30][31][32][33] The obtained results are in good accordance with histological sections of the animals' retinae. 34 The application of OCT technology in rodent models, however, is still challenging, mainly because of the small size of the rodents' eyes.…”
Section: Introductionsupporting
confidence: 81%
“…(Lye-Barthel et al, 2013; Sun et al, 2013; Tehrani et al, 2014) Implementation of AO strategies for overcoming challenges inherent to imaging rat and especially mouse eyes by OCT (and SLO) may also become important to ONH assessment in EG models. (Geng et al, 2012; Geng et al, 2009; Jian et al, 2013);Jian et al, Invest Ophthalmol Vis Sci 2014;55: E-Abstract 2083; Zhang et al, Invest Ophthalmol Vis Sci 2014;55: E-Abstract 2085.…”
Section: Introductionmentioning
confidence: 99%
“…(Leung et al, 2011; Walsh and Quigley, 2008) The addition of AO to compensate for optical aberrations enables imaging of RNFL structure in exquisite detail, with or without fluorescent contrast agents by SLO, or by OCT, including in the shorter eyes of small rodents. (Geng et al, 2012; Geng et al, 2009; Gray et al, 2008; Jian et al, 2013);[Jian et al, Invest Ophthalmol Vis Sci 2014;55: E-Abstract 2083; Zhang et al, Invest Ophthalmol Vis Sci 2014;55: E-Abstract 2085] AO-SLO and AO-OCT have recently been used to image RNFL bundles in human eyes, revealing fine detail in both healthy and damaged areas. (Chen et al, 2015; Huang et al, 2014; Kocaoglu et al, 2011; Kocaoglu et al, 2014b; Takayama et al, 2012; Takayama et al, 2013b) One interesting finding common to several of these recent AO studies is that reflectivity of RNFL bundles is often discrete, certainly more so than can be appreciated without AO (e.g., see Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Under "device type", choose Infrared (IR) mode. Note: It has been reported that the use of an external double aspheric lens can improve the image quality 1720 although we have no problem in obtaining high quality images by IV-ICGA without using external lenses (see representative results, Figures 1–4). …”
Section: Protocolmentioning
confidence: 66%
“…Wipe off excess PBS with a sterile cotton swab before ICGA recording. Other labs have used a contact lens to avoid dehydration of the cornea 1720 . …”
Section: Protocolmentioning
confidence: 99%